PENGHILANGAN BAU SECARA BIOLOGI DENGAN BIOFILTER SINTETIK - Herlambang, Arie (Jurnal Air Indonesia, 2005)
Biofilter as one of method processing of waste have been introduced since early 20, but in its application have time to be left by effect of newer technological appearance like trickling filter, rotating biological contactor, activated sludge, and fluidized bed reactor. Biofilter very effective in deodorizing, especially dangerous aromas of organic volatile compound, and poisonous air from industry with efficiency 90 - 99,9%. Biofiltrasion become more economic compared to carbon adsorption or oxidation when its organic content under 3000 ppm. Most biofilter operate on organic concentration around 1000 ppm or lower. There are some matter to influence market of biofilter, for example : 1). the increasing of regulation about oxide nitrogen emission coming from hot process. Biofilter do not yield nitrogen oxide addition, 2). The increasing of sigh of society about contamination of aroma of facility processing of waste, processing of solid waste and others, 3). preventive methodologies implementation of pollution using condensation and air emission concentration, 4). Pressure to industry to use processes with discard as small as possible, 5). The increasing of attention to emission of hit and organic air materials, and also low cost water treatment technology. Kata Kunci : Bau, Odour, Biofilter, Biofilm, Limbah tahu dan tempe, wastewater treatment